Penyuluhan Kesehatan Reproduksi Pada Siswa SMPN 24 Makassar - Pakadang, Sesilia Rante; Ratnah, St.; Salasa, Alfrida Monica (Jurusan Farmasi Politeknik Kesehatan Makassar, 2025)
Adolescents are individuals who are experiencing physical, psychological, and behavioral changes from childhood to adulthood. Teenagers are the future generation of the nation, so they need to be equipped with everything important to prepare for their future, including knowledge about reproductive health. The purpose of community service is to provide counseling to increase knowledge about reproductive organs and how to maintain reproductive health among adolescents. The activity methods are counseling, games, and discussions. The target audience of this program is grade VII students of SMPN 24 Makassar. Evaluation of activities with online pre-test and post-test questionnaires to assess the increase in participants' knowledge. The results of the activity demonstrated a high level of interest from the participants, as evidenced by their enthusiasm in participating in discussions and games, and an increase in knowledge, as indicated by the comparison of scores obtained in the pre-test and post-test. The conclusion is that there was an increase in participant knowledge from 27.6% to 96.5% after the counseling.Remaja adalah individu yang sedang mengalami perubahan fisik, psikis dan perilaku dari anak-anak menuju dewasa. Remaja adalah calon penerus generasi bangsa sehingga perlu dibekali segala hal yang penting untuk persiapan masa depannya termasuk pengetahuan tentang kesehatan reproduksi. Tujuan pengabdian adalah melakukan penyuluhan untuk meningkatkan pengetahuan tentang organ reproduksi dan cara menjaga kesehatan reproduksi pada kalangan remaja. Metode kegiatan berupa penyuluhan, games dan diskusi. Khalayak sasaran program ini adalah siswa kelas VII SMPN 24 Makassar. Evaluasi kegiatan dengan kuisioner pre test dan post test secara online untuk menilai peningkatan pengetahuan peserta. Hasil kegiatan menunjukkan minat yang baik dari peserta yang ditunjukkan oleh antusias peserta mngikuti diskusi dan games, peningkatan pengetahuan yang ditunjukkan oleh perbandingan nilai yang diperoleh pada pre test dan post test. Kesimpulan terjadi peningkatan pengetahuan peserta dari 27,6 % menjadi 96,5 % setelah penyuluhan.